Education: Quality VS Quantity. A Challenge to Link an d Match Policy - Emi Zulaifah (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 1996)
The issue on  Indonesia's Education has mostly been looked upon from quantitative point of view. Many report on  human resources  develop ment, especially  through the  educational agents, relied their analysis on  educational development quantitatively. Later in this writing,  I refer this orientation as  quantity oriented education.  As an  agent of people development, quantity orientation in  education is facing a critical point regarding its ability to prepare human resources for a new era  of International competition.